2011
DOI: 10.1002/alr.20051
|View full text |Cite
|
Sign up to set email alerts
|

Outcome results of endoscopic vs craniofacial resection of sinonasal malignancies: a systematic review and pooled‐data analysis

Abstract: Transnasal endoscopic resection appears to be a reasonable alternative to craniofacial resection in the management of low-stage sinonasal malignancies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
67
0
7

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(82 citation statements)
references
References 25 publications
3
67
0
7
Order By: Relevance
“…A systematic review of the literature by Higgins et al (24) on the results of craniofacial versus endoscopic resection of sinonasal malignancies revealed that endoscopic management of sinonasal cancers appears to be a promising approach in treatment of low-staged esthesioneuroblastomas and adenocarcinomas. In the present study, 85% of patients were treated with craniofacial resection.…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review of the literature by Higgins et al (24) on the results of craniofacial versus endoscopic resection of sinonasal malignancies revealed that endoscopic management of sinonasal cancers appears to be a promising approach in treatment of low-staged esthesioneuroblastomas and adenocarcinomas. In the present study, 85% of patients were treated with craniofacial resection.…”
Section: Discussionmentioning
confidence: 99%
“…Several reviews and meta‐analyses comparing outcomes between endoscopic and open CFRs have shown at least equivalent survival data. A systematic review and pooled‐data analysis of 226 patients demonstrated that there was no difference in survival outcomes between endoscopic and traditional CFR for T1 and T2 sinonasal malignancies . Patients in this study were identified from 15 case studies reporting outcomes for esthesioneuroblastoma, adenocarcinoma, and sinonasal undifferentiated carcinoma.…”
Section: Comparison Of Endoscopic Versus Traditional Cfrmentioning
confidence: 99%
“…Complications of open or endoscopic approaches include cerebrospinal fluid leaks and sequalae, cranial nerve injuries, and hemorrhage. Open and CEA approaches have additional morbidity associated with performing a craniotomy . Additionally, the EEA avoids facial incisions and potential cosmetic issues that arise from lateral rhinotomy and coronal incisions.…”
Section: Introductionmentioning
confidence: 99%
“…Малое количество наблюдений не позволяет сделать вывод о целе-сообразности лучевого лечения у этой категории пациентов. Отдельные исследователи утверждают, что эндоназальное удаление опухоли на ранних стадиях не только положительно сказывается на качестве жизни, но и не ухудшает онкологического прогноза [1,11]. У 3 из 4 пациентов с распространением ЭНБ в полость черепа выполнено трансназальное эндоскопическое удаление опухоли, при котором в 2 случаях потребовалось проведение пластики дефекта твердой мозговой оболочки.…”
Section: Discussionunclassified
“…Лечение пациентов с ЭНБ включает химиотерапию, лучевую терапию и хирургическое вмешательство. При опухоли, локализованной в полости носа и решетчатом лабиринте (I, II стадия по TNM и А-стадия по Kadish-Morita), проводится, преимущественно, эндоскопическое трансназаль-ное удаление [11]. Химиотерапевтическое лечение назначается как в неоадъювантном режиме, так и в послеоперационном периоде при распростра-ненных стадиях опухоли.…”
unclassified